Gender, and Religion: The Typology of Female Names in Sudan - Hazaymeh, Omar Mohammad-Ameen Ahmad (Onomástica desde América Latina, 2025)
This study aims to analyze the impact of Islam on the choice of female names in Sudan through a semantic analytical approach to explore female names associated with Islam from a cultural and religious perspective. The research’s motivation stems from the significant role that names play in identity formation and the transmission of cultural and religious values. Despite the extensive body of literature on Islamic naming traditions, little attention has been given to the specific case of Sudan. This study hopes to contribute in showing how Islam affects names in Sudanese society. To achieve this, female names associated with Islam were collected from various Sudanese regions to shed light on their types. As for the methodology, after collecting the names they were categorized under headings to show the Islamic sources from which they were taken. The study relied on the works in the theoretical framework about names in their cultural, social and religious contexts and those explore Islamic and Arabic onomastics. The findings reveal that many Sudanese female names are deeply rooted in Islamic heritage, reflecting moral and spiritual values that parents wish to instill in their children. Some names are intentionally chosen to affirm religious identity, reinforcing the connection between personal identity and the broader Islamic religious framework. This research contributes to the field by highlighting the impact of religion in naming practices. It reflects the importance of raising awareness about the socio-religious significance of names and recommends integrating these discussions into educational curricula. The study calls for initiatives that encourage parents to engage with Islamic heritage in naming their children while also considering the broader cultural and historical dimensions of Sudanese society and to promote a deeper understanding of the cultural and religious significance of names in shaping identity, social belonging, and conveying religious values.